2021
DOI: 10.1111/ejn.15453
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dynamics: A potential proxy of neural preparation for goal‐directed eye movement

Abstract: The pupils reflexively constrict or dilate to regulate the influx of light on the retinae. Pupillary light reflex (PLR) is susceptible to many non-visual cognitive processes including covert orientation of attention and planning rapid saccadic eye movement. The frontal eye field (FEF) and superior colliculus (SC), which also send projections to the PLR pathway, are two important areas in primate's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 134 publications
(157 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, recent studies questioned whether the observed facilitation in visual discrimination at the location of an imminent saccade was due to pre-saccadic orientation of attention or by means of the consolidation of visual short-term memory following the orientation of gaze ( Born et al, 2013 ; Huber-Huber et al, 2021 ). Our data suggest that pre-saccadic orientation of attention did not contribute to the modulation of visually evoked pupillary responses, suggesting no high-level perceptual benefit from pre-saccadic pupillary constriction except the prevention from overwhelming visual transients on the fovea during the gaze-fixation-gaze cycle in a naturally heterogenous visual world ( Mostofi et al, 2020 ; Pandey and Ray, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Furthermore, recent studies questioned whether the observed facilitation in visual discrimination at the location of an imminent saccade was due to pre-saccadic orientation of attention or by means of the consolidation of visual short-term memory following the orientation of gaze ( Born et al, 2013 ; Huber-Huber et al, 2021 ). Our data suggest that pre-saccadic orientation of attention did not contribute to the modulation of visually evoked pupillary responses, suggesting no high-level perceptual benefit from pre-saccadic pupillary constriction except the prevention from overwhelming visual transients on the fovea during the gaze-fixation-gaze cycle in a naturally heterogenous visual world ( Mostofi et al, 2020 ; Pandey and Ray, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
“…In the current context, eCFD in the CCP task was determined using a decision cue in the form of an array of square checker boxes (each of size ∼2.5° × 2.5° at an eccentricity of ∼12°), whereas in the CCC task, a thin broken annular decision cue with a small outer (∼1.8°) and inner (∼1.6°) radius determined eCFD. We simulated a biomechanical model of pupillary aperture ( Usui and Hirata, 1995 ; Pandey and Ray, 2021 ) with the two different stimulus strengths in an arbitrary unit, which we referred to as an effective CFD or eCFD. Simulated data mimicked the observed data, in support of the possibility of a critical contribution from selective attention in modulating pupil size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations